El neoplatonismo en María Zambrano. La carne de las sombras - Sánchez Madrid, Nuria (Pontificia Universidad Católica del Perú, 2025)
This paper explores the impact of Maria Zambrano’s acquaintance with Neoplatonic sources of Late Antiquity in her thought. The objectives of this investigation are twofold: first, to conduct an in-depth study of a lesser-known source of Zambrano’s legacy; and, second, to explore the reasons behind the current interest on thinkers like Plotinus, particularly in light of the significance of the struggle between intelligence and corporality within the Enneads. The paper has three main sections. Firstly, I present Zambrano’s vindication—on a plebeian key—of the figure of Plotinus, which aligns with the views of Cuban poets that were part of her circle during her early exile, such as Fina García Marruz, and is closely related to her—more extensively studied—recovery of Stoicism. Then, I contextualize the use of Plotinian motifs within the Neopythagorean path, a path that Zambrano considered a fundamental element of her thought throughout her whole life. Finally, I focus on Zambrano’s texts dedicated to the discussion of Plotinus and analyze the contribution of this thinker of Late Antiquity to the reflection on the contemporary historical condition.

Este artículo se ocupa de explorar la huella que el conocimiento de las fuentes del neoplatonismo tardoantiguo dejó en el pensamiento de María Zambrano, con la intención doble de profundizar en una fuente poco conocida del legado zambraniano y de abordar los motivos que evidencian el interés contemporáneo hacia pensadores como Plotino, en virtud de la centralidad que posee en las Enéadas el combate entre la inteligencia y la corporalidad. El trabajo se articula en tres partes. En primer lugar, expongo la reivindicación en clave plebeya que Zambrano realiza de la figura de Plotino, en sintonía con poetas cubanos pertenecientes a su círculo en el temprano exilio como Fina García Marruz, en una línea afín a su más conocida recuperación del estoicismo. En segundo lugar, contextualizo el recurso a motivos procedentes de Plotino en el marco de la senda neo-pitagórica que Zambrano siempre consideró como una de las coordenadas vertebradoras de su pensamiento. En tercer lugar, me aproximo a escritos en los que Zambrano se ocupó centralmente de la figura de Plotino y de la contribución que este pensador tardoantiguo ofrece para reflexionar sobre la condición histórica contemporánea.
Maria Zambrano’s Neoplatonism. The Flesh of the Shadows
Keywords: Zambrano; Plotinus; Neoplatonism; Neopythagoreanism; Poetry; Zambrano; Plotino; Neoplatonismo; Neopitagorismo; Poesía; https://purl.org/pe-repo/ocde/ford#6.03.01